A qualitative study of the views of adolescents on their caries risk and prevention behaviours. Issue 1 (December 2015) - Hall-Scullin, Emma; Goldthorpe, Joanna; Milsom, Keith; Tickle, Martin
Abstract Background The purpose of this study was to explore the attitudes and beliefs of adolescents towards dental caries and their use or non-use of caries prevention regimens. Methods Adolescents aged 16 years from four state-funded secondary schools in North West of England (n = 19). Purposive sampling strategically selected participants with characteristics to inform the study aims (gender, ethnicity, and caries status). Semi-structured interviews were transcribed verbatim and analysed using a framework approach. Results 14 codes within five overarching themes were identified: "Personal definition and understanding of oral health"; "Knowledge of oral health determinants"; "Influences on oral health care"; Reason for oral health behaviours"; and "Oral health in the future". Adolescents conceptualise oral health as the absence of oral pathology and the ability to function, which included an aesthetic component. Appearing to have healthy teeth was socially desirable and equated with positive self-image. The dominant influence over oral health behaviours was habitual practice encouraged by parents from a young age, with limited reinforcement at school or by dental practices. At this transitional age, participants recognised the increasing influence of peers over health behaviours. Self-efficacy pertained to diet modification (reduction in sugar-ingestion) and oral hygiene behaviour (tooth-brushing). A lack of understanding of caries aetiology was evident. Behaviours were mitigated by a lack of environmental support; and a desire for immediate gratification often overcame attempts at risk-reducing behaviour. Conclusions Parents primarily influence the habitual behaviours of adolescents. With age, the external environment (availability of sugar and peers) has an increasing influence on behaviour. This suggests that to improve adolescent health, oral health promoters should engage with parents from early childhood and create supportive environments including public policy on sugar availability to encourage uptake of risk-minimising behaviours.